Comparative metabolomics reveals differences in primary and secondary metabolites between "Shixia" and "Chuliang" longan (Dimocarpus longan Lour.) pulp. Issue 10 (28th August 2021) - Lai, Tingting; Shuai, Liang; Han, Dongmei; Lai, Ziying; Du, Xinxin; Guo, Xiaomeng; Hu, Wenshun; Wu, Zhenxian; Luo, Tao
Abstract: Longan was a characteristic fruit for both medicine and food in China, which was rich in primary and secondary metabolites. Comprehensive high‐throughput identification and comparison of metabolites in longan pulp among different varieties were still lacked. "Shixia" (SX) and "Chuliang" (CL) were the biggest major cultivars of longan in China. In this study, the content of total soluble solid, total flavonoid, and total phenolics indicated the difference of sweetness and bioactive compound content between the SX and CL pulp. Through a widely targeted metabolome, a total of 514 metabolites were identified and categorized into 23 groups mainly including flavonoids, amino acids & derivatives, lipids, phenolic acids, nucleotides & derivatives, alkaloids, organic acids and sugars & derivatives. A total of 89 metabolites with significantly differential accumulation (variable importance in projection (VIP) value ≧1, p ‐value <.05) over 1.2 fold were found between SX and CL, which were mainly enriched into pathways including flavone and flavonol biosynthesis, glycolysis/gluconeogenesis, and arginine and proline metabolism. Higher leveled hexose and hexose‐phosphate (i.e., β‐D‐glucose, D(+)‐glucose, glucose‐1‐phosphate and glucose‐6‐phosphate), dominant organic acids (i.e., citric acid, succinic acid, D‐malic acid, and citramalate), and essential amino acids (L‐threonine, L‐valine, L‐isoleucine, L‐leucine, L‐phenylalanine and L‐lysine) in SX pulp might be contributed to the taste and flavor difference between SX and CL. Moreover, the greatly differential accumulated secondary metabolites especially flavonoids and phenolic acids might result in different medicinal and nutritional characteristic between SX and CL. In conclusion, this study provided a systemic metabolic basis for understanding the nutritional differences between SX and CL and would help deepen the molecular biology and pharmacology research on characteristic metabolites in longan pulp. Abstract : A total of 514 metabolites were identified in SX and CL longan pulp and categorized into 23 groups by a widely targeted metabolome. A total of 89 significantly differential accumulated metabolites were found between SX and CL, which were mainly enriched into pathways including flavone and flavonol biosynthesis, glycolysis/gluconeogenesis, arginine, and proline metabolism. The greatly differential accumulated secondary metabolites especially flavonoids and phenolic acids might result in different medicinal and nutritional characteristic between SX and CL.